The Impact of Video Based Health Education on Sundanese Mothers Perceptions of Parenting Practices for Toddlers - Hartiningrum, Chanty Yunie; Danefi, Tupriliany; Fitriani, Sinta (Inspirasi Foundation, 2024)
Introduction: Parenting during infancy and toddlerhood plays a crucial role in shaping children's physical, social, and intellectual development, with effective parenting during these early years having long-lasting effects on a child’s health and independence. Cultural values and family traditions influence parenting practices, and educational media, such as videos, can improve perceptions and behaviors by engaging audiences and providing relevant, contextual information. Objective: This study aims to determine the influence of health education through video media on the perception of mothers with infants under five about parenting patterns in the Sundanese ethnicity in Cikunir Village. Method: This quantitative study employs a quasi-experimental design to assess the impact of video-based health education on mothers' perceptions of toddler parenting. The population consists of mothers with children aged 0-60 months in Cikunir Village, with purposive sampling used to select 57 participants. Data were presented in tables, and descriptive and analytical analysis was performed using pre-test and post-test questionnaires. Result: Statistical analysis revealed a significant effect of health education on mothers' perceptions, with a p-value of 0.000, indicating a statistically significant result (p < 0.05). Conclusion: Health education through video media significantly influences mothers' perceptions of parenting patterns in the Sundanese ethnic group. Early intervention in child growth and stunting prevention is essential for promoting age-appropriate development in infants.